Exergy and environmental assessment of R-290 as a substitute of R-410A of room air conditioner variable type based on LCCP and TEWI approaches - Angel Andrade; Juan Zapata-Mina; Alvaro Restrepo (Results in Engineering, 2024)
The global energy demand and associated emissions from air conditioning systems are expected to triple by 2050. These systems not only represent high energy consumption but also have an environmental impact due to the emission of greenhouse gases from the use of refrigerants. This paper presents an exergy and environmental assessment of variable-type room air conditioner based on Life Cycle Climate Performance (LCCP) and Total Equivalent Warming Impact (TEWI) approaches. For this, three test units were tested at the Air Conditioning Testing Laboratory (LPEA) from the Technological University of Pereira (UTP). The results showed that the method of calculating indirect emissions from annual energy consumption (AEC) influences TEWI results, emphasizing the need to consider operational conditions. Despite R-290 environmental advantages, adjustments in AEC revealed a 50 % difference, highlighting the benefits of new refrigerants over variable-speed technologies. The proposal of exergenvironmental analysis analysis proved crucial, showcasing R-290 advantages, while underscoring risks associated with its flammability, As well as the effect of the possibilities of improving the design of some components to improve the overall energy efficiency of the system.